FREE FATTY ACIDS PROFILING IN RESPONSE TO CARNITINE SYNERGIZE WITH LUTEIN IN DIABETIC RATS - AL-Malki, Abdulrahman L; Moselhy, Said S (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The objective of this study was to investigate the fatty acids profiling in diabetic rats induced by sterptozocine (STZ)and their response to administration of lutein and carnitine.Materials and methods: Ninety male albino rats were divided into 6 groups as follows: Normal control. The remaining rats wereinjected i.p a single dose of STZ (65 mg /kg bw) for induction of diabetes. Diabetic rats were grouped as: GP II: (Untreated): GP III:Rats were given orally with L-lutein (100 mg/kg bw).GP IV: Rats were given carnitine (30 μg/kg) i.p. GP V: Rats were givencarnitine and lutein GP VI were given metformin (100mg/kg bw/d) for 6 weeks.Results: Treatment of diabetic rats with lutein, L-carnitine, combined decreased the levels of glucose, HA1C compared withuntreated diabetic (p<0.001). Administration of L-lutein, carnitine, combined to normal rats significantly decreased the levels ofmyristic, palmitice, palmitoleic, stearic, linoleic, α-linolenic, arachidic and eicosadienoic when compared with control normal rats(p<0.001).Conclusion: Abnormalities of fatty acids composition was observed in diabetic rats. Combination treatment with lutein and carnitinecould ameliorate deleterious effect induced by STZ and attenuate the changed fatty acid composition